Inhibition of lens-induced myopia in guinea pigs using a far-induced infrared ray material - Weiwei, Xu; Jingxi, Liu; Erti, Guoji; Xinrun, Zhou; Yifei, Huang (Frontiers in Medicine, 2025)
PurposeNumerous studies have demonstrated a close relationship between choroidal thickness (ChT), sclera/choroidal hypoxia, and the onset and progression of myopia. Far-infrared (FIR) therapy is a traditional method used to enhance microcirculation. In this study, we estimated the effectiveness of FIR in myopia control and explored its underlying mechanisms. Furthermore, we compared the efficacy of FIR from two different sources in controlling myopia.MethodsGuinea pigs were divided into three groups, all of which underwent minus lens induction for 4 weeks. Two of the groups received simultaneous FIR intervention, either from a FIR radiator (FIRR) lamp or from an innovative FIR material (FIRM). Refraction, axial length (AL), ChT, and levels of hypoxia-labeled pimonidazole in the choroid and sclera were measured.ResultsBoth FIRR and FIRM inhibited increases in refraction and AL and attenuate the decrease in ChT. They also mitigated choroidal and scleral hypoxia. Compared to FIRR, FIRM demonstrated a greater effect on myopia control and hypoxia attenuation. However, the difference in AL reduction between the two FIR sources was not statistically significant.ConclusionFIR effectively controls myopia, and the innovative FIR material may represent a breakthrough in myopia management in the near future.